Querfurti Brúnó és a fekete magyarok - Tóth Sándor László (Belvedere Meridionale, 2012)
In this study the author treats the problem, who were the Black and White Hungarians, why they were named so, where they lived. Altogether six passages of three sources deals with them, and five passages refer to the Black Hungarians and just two passages mention the White Hungarians. Our main source, Bruno of Querfurt in his biography on the Polish hermits (written about. 1006-1008) mentioned that he had went to the Black Hungarians and tried to convert them, but in vain. In his letter (about 1008/1009) addressed to the German king, Henry II. he noted that he had heard about the full conversion of the pagan Black Hungarians by force. Ademar of Chabanne in his chronicle (written about in 1030) referred to White Hungary differentiating it from Black Hungary, whose inhabitants are black as the Ethiops. In another passage he told that King Stephen of Hungary attacked and converted Black Hungary. In the Russian Primary Chronicle (PVL) there is a reference to White Ugrians in the 7th century, and there is another reference to Black Hungarians marching beside Kiev at about the end of 9th century. In historical research there is a theory, that these colours denote ethnical differences. The White Hungarians were the seven Hungarian tribes, while the Black Hungarians were the joining Kabars/Kavars of Khazar origin. It was also supposed that the White Ugrians were the first conquerors of the Carpathian basin about 670/680, while the Black Ugrians were the Turkish people of the conquering Árpád in 895. Another hypothesis maintains that the colours refer to political/tribal differences; the White Hungarians represent the ruling clans/tribes (King Stephen) and the Black Hungarians were the eastern, opposing tribes (Koppány, Gyula and Ajtony etc.). It was supposed that these colours referred to the Christian (white) and pagan (black) differences. Our sources mentioned can not solve this mystery. Bruno of Querfurt really knew them, tried to convert them and heard about their final Christianization. He did not make any distinction between Hungarians and Black Hungarians. Adémar never came to Hungary, just heard about a war in Hungary and connected it with the Black Hungarians. He probably mentioned a frequently used medieval topos in connection with the colour of the Black Hungarians. The White Ugrians of the Russian Primary Chronicle were probably Turks, Khazars or Onogurs, while the Black Hungarians were the Hungarians/Magyars on their way to the Carpathian basin. The author of this study uses a contemporary analogy based on „De administrando imperio” of emperor Constantine VII (written about 950). The emperor refers to White Serbs, White Croatians and Black Bulgars in his work. The White Serbs and White Croatians were living noth of the Carpathian basin and other Serbs and Croatians were living south of it. The Byzantine emperor also mentions that the unbaptised White Croatia were also called Great (old, ancient) Croatia, the original homeland of the Croats. Using this analogy the author maintains that the ancient homeland of the Hungarians, „Magna Hungaria” or „Ungaria Maior” (Baskiria) could be also called White Hungary, while the conquering Hungarians of Árpád, who settled first in Etelköz, then in the Carpathian basin, were probably called Black Hungarians as well. The other seceding Hungarian group settling in the Caucasus were called savarti, which means „black boys” according to emperor Constantine VII (De Cerimoniis). So White Hungarians and Black Hungarians denote people remaining in the ancient homeland and settling in new homeland(s). Bruno of Querfurt met just the Black Hungarians and heard about just them, who were the conquering seven tribes of Hungarians/Magyars.